(untitled) (The New Uzbekistan Journal of Medicine, 2025)
This article examines the concept of ecologically clean and green products, emphasizing their importance in sustainable development and environmental protection. The study explores how technological advancements influence the production and consumption of green products, analyzing both positive and negative impacts. While innovation has led to more efficient and sustainable manufacturing processes, some technological developments still pose environmental risks. The research highlights the role of government policies, corporate responsibility, and consumer awareness in promoting eco-friendly products. The findings suggest that a balanced approach to technological progress and environmental sustainability is essential for a greener future.